Experimental study of the noise radiated by an air flow discharge through diaphragms and perforated plates. (10th November 2018) - Laffay, P.; Moreau, S.; Jacob, M.C.; Regnard, J.
Abstract: An experimental analysis of the noise radiated by a high pressure flow discharge through diaphragms and perforated plates is carried out for a large range of subsonic and supersonic operating conditions (nozzle pressure ratio (NPR) from 1 to 3.6). A parametric study of the geometrical parameters is also achieved to characterize their influence onto the acoustic radiation and ways to reduce it. This reaches from single diaphragms to multi-perforated plates with variable hole diameters and arrangements that are placed at the exit of a duct. Different acoustic behaviors are observed: in all cases the far-field acoustic radiation is dominated by a broadband contribution associated with the turbulent mixing in shear layers. In the diaphragm cases, this broadband noise has similar characteristics as the mixing noise of classical unheated jets while in the multi-perforated plates cases, it is composed of two distinct humps associated with different parts of the jets development. For supersonic regimes, in addition to this broadband radiation, shock associated noise (screech and broadband shock associated noise) appears for all diaphragm cases and for the perforated plate with the closest holes. Finally for the smallest NPR, a high frequency tonal noise has been observed in most of the multi-perforated cases and for the smallest diaphragm. Different regimes of this radiation have also been observed with a possible amplitude modulation of the dominant tone. This radiation may be attributed to vortex shedding due to the sharp section reduction that would trigger a flow resonance between the small ducts of the holes and their sharp edges.